Zooplankton community attributes in an oligo-mesotrophic reservoir: A comparative study of two sampling strategies - RAFAEL L. MACÊDO; VANESSA G. LOPES; BETINA KOZLOWSKYSUZUKI; CHRISTINA W.C. BRANCO (Anais da Academia Brasileira de Ciências, 2018)
Abstract Studies of the limnetic zooplankton in Brazilian freshwater have been done using several sampling strategies which are frequently associated to personal preferences, system constraints and objectives of the studies. It is known that a better sampling technique exists for each group of investigated zooplankton. So, the challenge is to provide a good sampling method for all groups at once. Regarding this theme we are contributing by pointing out the merits and demerits of two collecting methods of zooplankton widely used in many studies in Brazilian reservoirs to clarify the information about communities’ structure in past published and non-published biological data and also find a more useful sampler for future studies. Two simultaneous strategies were used with a 68μm-plankton net: filtration of water collected at sub-surface by bucket and vertical hauls throughout the euphotic zone. A total of 133 taxa was found with both strategies. Rotifers (69 taxa) comprised the group with the highest richness, followed by protozoans (31 taxa), cladocerans (30 taxa) and copepods (5 taxa). Paired t-tests showed significant difference for richness despite none for density in whole period. Spatially, sampling strategies differed in abundance and composition of zooplankton at most sites sampled (except for L1- shallowest site and L4 – deepest site). Temporally, both samplers showed the highest mean abundances at thermal stratification period. In general, the extent of spatial data collected throughout the vertical gradient provided better estimations in the limnetic area for the attributes analyzed: zooplankton density, richness, specific diversity, equitability and cumulative richness. Zooplankton sampling by vertical hauls through the euphotic zone was more efficient, but in order to obtain integrated data and according to the collector’s curve it might be useful to adopt both methodologies.